Organizational justice, justice climate, and somatic complaints: A multilevel investigation - Herr, Raphael; Bosch, Jos A.; Loerbroks, Adrian; Genser, Bernd; Almer, Christian Alexander; Van Vianen, Annelies E. M.; Fischer, Joachim E. (Journal of psychosomatic research, 2018)
Objective - Organizational justice refers to perceived fairness at the workplace. Individual perceptions of injustice have been linked to reduced mental and physical health. However, perceptions of injustice also exist at the aggregate level of departments, reflecting a shared perception, denoted as justice climate. There is evidence that this shared perception independently predicts individual distress levels (e.g., anxiety, depression), which might negatively affect somatic symptom perception and reporting. Hence, the objective of this study was to examine whether individual perceptions of poor justice as well as a poor justice climate are related to elevated somatic complaints. In addition, this study examined if justice climate moderates the relationship between individual-level justice perceptions and somatic symptom reporting. - Methods - Cross-sectional data from a large industrial manufacturing company was used, involving 1,102 employees in 31 departments. A validated scale covering interactional and procedural justice assessed individual-level organizational justice. A 19-item symptom checklist measured somatic complaints. Multilevel analyses estimated individual-level associations (within-department effects) with somatic complaints, department-level associations (between-department effects), and the cross-level interaction of both. - Results - Individual-level justice perceptions were negatively associated with somatic complaints. Collective justice climate was likewise significantly associated with somatic complaints. There was no indication for a moderation effect of justice climate. - Conclusion - A poor justice climate correlated positively with individual somatic complaints while controlling for individual perceptions, i.e., above and beyond individual justice perceptions. These findings may imply that interventions targeting department-level perceptions of justice may have the potential to reduce individual somatic complaints beyond the effects of individual-level interventions.